Pengaruh Nilai-Nilai Islam, Upah, Pengembangan Karir, Dan Motivasi, Terhadap Kinerja Karyawan Pada Bank Sumut Kantor Cabang Syariah Medan - Putri Nazli; Marliyah Marliyah; Yenni Samri Juliati Nasution (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine Islamic values, wages, career development, and motivation, on employee performance at Bank Sumut Syariah Medan Branch Office. In this study, researchers used quantitative methods by processing primary data through questionnaires given to employees of Bank Sumut, Medan Syariah Branch Office as many as 77 respondents with sampling techniques, namely saturated samples and associative methods to test the relationship between variables. The data obtained were processed using SPSS Version 22 and analyzed using multiple regression analysis. The analysis used includes instrument validity and reliability tests, statistical tests which include t-test, f-test, and classical assumption test which includes normality test, multicollinearity, and heteroscedasticity test. Based on the output results of SPSS version 22, it shows that the variable x2 (wages) has a positive and significant effect on the Y variable (employee performance) because the t-count value is 13,843 > t table 1.66543 and is significant 0.000